APPLICATION OF EMOTIONAL FREEDOM TECHNIQUE TO REDUCE ANXIETY IN PATIENTS WITH GANGRENE WOUNDS - Nadia Sintia Wardany; Wawan Rismawan; Talitha Agripina Salsabilla; Deti Widi Astuti (Bajang Institute, 2024)
Background: Psychological problems such as anxiety are one of the most common problems in the world. Non-pharmacological interventions are one of the most needed treatments to help patients overcome their anxiety, one of which is the emotional freedom technique (EFT). EFT can be effectively learned through health counseling to increase knowledge and self-help skills. Objective: It is expected that this service will be able to increase the knowledge and skills of the community in controlling anxiety. Methods: Conducted through direct face-to-face meetings for the delivery of health information by the speaker at one of the participants' homes. Results: The target group can understand the concept of anxiety disease and can apply emotional freedom technique therapy independently as a treatment. There is also a significant change in the level of anxiety in the target group after being given emotional freedom technique therapy